ANALISA KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA TERNAK SAPI POTONG JENIS PERANAKAN LIMOSIN - Abdur Rahim; Martono Achmar (Program Studi Agribisnis Fakultas Pertanian, 2016)
The research objective was to determine the feasibility of beef cattle types of limousines in the village Mlandingan Wetan, determine the business development strategy cattle at the type of limousine in the village Mlandingan Wetan. The statistical analysis used is descriptive analysis, which is a method used to analyze data in ways that describe or depict the data that has been collected as without intending to make conclusions apply to the public. Sampling in this study using census method, which is taking a population to be sampled, the population of beef cattle breeder type of limousine as many as 34 farmers. The results showed that the eligibility for the beef cattle business is done in the village Mlandingan Wetan District of Bungatan not feasible to develop. Based on the analysis of B / C ratio obtained reaches 0:09 so that the cattle business is not feasible to develop. Factors causing the cattle business is not worth the price of cow fluctuations, the cost of purchasing feed and labor. Based on the SWOT matrix mapping, business development strategies of cattle in the village Mlandingan Wetan is diversification strategy because it is located in quadrant 2, This situation means that the cattle business in the village Mlandingan Wetan face many threats but still have the power so that the strategy used was to use force to take advantage of business opportunities in cattle. Suggestions of researchers are preferably beef cattle farmer in the village of Mlandingan Wetan increase production and quality of livestock, in order to keep prices and demand remain high and maintain a working relationship with the government of Situbondo. The Government should give the development, empowerment and institutional development group of farmers through extension workers in order to increase the income of farmers.